Georgij Efron: Tagebücher. Band II. (1941-43) (Hollitzer, 2022)
The Diaries, Volume II, continue after the death of Marina Tsvetaeva, he returns to Moscow, where he could stay with aunt Lilja, a sister of his father, living off from selling items that he inherited from his mother. At that time Moscow was undergoing air raids; the situation was devastating and became more and more chaotic. He feared to get drafted for work at the defense wall. So, he decided to join a transport of the Union of Soviet Writers to Uzbekistan. The Diaries of Georgij Ėfron may be considered a singular historical document, nobody dared to put down in writing freely and uncensured unorthodox thoughts and commentaries about the deplorable and miserable condition of the Soviet society and the hardship of a life as an evacuee in the hinterlands. His notes are of an astonishing high literary quality as well. Volume 1: http://e-book.fwf.ac.at/o:1775 Volume 2: http://e-book.fwf.ac.at/o:1776